Assessment of Some Trace Elements in Workers’ Blood in Fuel Stations in Al-Nasiriyah City - Altai,ZainabSabbar Kadhem; Afrah Abid Maktoof (University of Thi-Qar Journal of Science, 2024)
Environmental pollution has become a major problem in the world, especially due to the rapid development of industries related to hydrocarbons such as fuels and polluting products. This situation is considered a serious threat to the environment and people due to its impact on human health and other living things. This study aimed to assess the trace element levels (Lead, Cadmium, Nickel, Arsenic) in the serum of workers in the fuel stations in central region of Thi-Qar Province. 60 people were selected from a group of workers in the age category (19 to 50 years), with work experience (1 to 5 years), some of whom were smokers and others were non-smokers. The study involved workers from three stations: ( Al-Raya, Al-Noor, and Thi-Qar). Control group incorporated from university students who were working remotely. The measurements were conducted at the laboratories of the Southern Technical College at Thi-Qar University. The statistical analysis revealed that the levels of the four metals (Pd >Ni > As > Cd) in individuals working at fuel stations are higher compared to the control group. In addition, the concentration of these metals in the blood of smokers is higher than that of non-smokers. The study also confirmed that all trace elements increase in the autumn season. Compared to the winter season, the concentration of trace elements in the autumn season was (20.3, 2.425, 2.068, 0.2.7) μg/dl, while their concentration in the winter was (14.4, 1.339, 1.218, 0.129) μg/dl. T